Evaluasi Usability pada Sistem Informasi Akademik menggunakan Metode Usability Testing (Studi Kasus : STIE Widya Gama Lumajang) - Rizal Bachtiar; Satrio Hadi Wijoyo; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
STIE Widya Gama Lumajang Academic Information System (SIAKAD Wiga) is a means of managing academic activities regarding lectures and delivering structured and integrated information to users including lecturers and students. The system has never been evaluated on system usability. The purpose of research on SIAKAD Wiga is to find problems experienced by users when interacting with the system using Usability Testing and interviews and then design improvements to SIAKAD Wiga as a form of interface comparison. This study uses 8 respondents by dividing 2 types of lecturer and student users based on the intensity using by the system. From the results of interface improvements, an increase in usability test results on the learnability matrix by 2.0 dropped to 1.7 for lecturer users and by 1.5 dropped to 1.4 for student users. Matrix efficiency by 53% increase to 100% for lecturer users and by 86% increase to 100% for student users. The memorability matrix at the initial evaluation with an average number of clicks and an average working time of 48 clicks and 451.5 seconds dropped to 46 clicks and 223.5 seconds for lecturer users and by 50 clicks and 176.5 seconds dropped to 45 clicks and 121 seconds for student users. Matrix errors of 1.92% dropped to 0% for lecturer users and 9.84% dropped to 0% for student users. The satisfaction matrix at the initial evaluation of 40.62% increase to 76.25%.